Palestinian Economic Prospects : Gaza Recovery and West Bank Revival - World Bank (Washington, DC, 2017)
In its report to the September 22, 2008 meeting of the Ad Hoc Liaison Committee (AHLC), the World Bank noted that the Palestinian Authority (PA), Israel, and the international donor community made some progress on the three parallel conditions for Palestinian economic revival, albeit to different degrees. The report notes the dramatic impact of Israel s recent three-week offensive in Gaza and analyzes the variety of recovery and reconstruction schemes being explored by the donor community. We find that these have not yet led to any significant impact on the ground due to the continued closure imposed on Gaza. The devastation in Gaza, coupled with a fluid political environment in both the PA and Israel, has made it necessary for this report to revisit the fundamentals of donor support to the PA in view of the long-term goal of establishing an economically viable Palestinian state independent of external aid. Examination through this lens reveals a fundamentally flawed picture.